Patterns of non-communicable comorbidities at start of tuberculosis treatment in three regions of the Philippines: The St-ATT cohort. - Sharon E Cox; Tansy Edwards; Benjamin N Faguer; Julius P Ferrer; Shuichi J Suzuki; Mitsuki Koh; Farzana Ferdous; Naomi R Saludar; Anna-Marie C G Garfin; Mary C Castro; Juan A Solon (Public Library of Science (PLoS), 2021)
Diabetes and undernutrition are common risk factors for tuberculosis (TB), associated with poor treatment outcomes and exacerbated by TB. Limited data exist describing patterns and risk factors of multiple comorbidities in persons with TB. Nine-hundred participants (69.6% male) were enrolled in the Starting Anti-TB Treatment (St-ATT) cohort, including 133 (14.8%) initiating treatment for multi-drug resistant TB (MDR-TB). Comorbidities were defined as: diabetes, HbA1c ≥6.5% and/or on medication; hypertension, systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg and/or on medication; anaemia (moderate/severe), haemoglobin <11g/dL; and, undernutrition (moderate/severe) body-mass-index <17 kg/m2. The most common comorbidities were undernutrition 23.4% (210/899), diabetes 22.5% (199/881), hypertension 19.0% (164/864) and anaemia 13.5% (121/899). Fifty-eight percent had ≥1 comorbid condition (496/847), with 17.1% having ≥2; most frequently diabetes and hypertension (N = 57, 6.7%). Just over half of diabetes (54.8%) and hypertension (54.9%) was previously undiagnosed. Poor glycemic control in those on medication (HbA1c≥8.0%) was common (N = 50/73, 68.5%). MDR-TB treatment was associated with increased odds of diabetes (Adjusted odds ratio (AOR) = 2.48, 95% CI: 1.55-3.95); but decreased odds of hypertension (AOR = 0.55, 95% CI: 0.39-0.78). HIV infection was only associated with anaemia (AOR = 4.51, 95% CI: 1.01-20.1). Previous TB treatment was associated with moderate/severe undernutrition (AOR = 1.98, 95% CI: 1.40-2.80), as was duration of TB-symptoms before starting treatment and household food insecurity. No associations for sex, alcohol or tobacco use were observed. MDR-TB treatment was marginally associated with having ≥2 comorbidities (OR = 1.52, 95% CI: 0.97-2.39). TB treatment programmes should plan for large proportions of persons requiring diagnosis and management of comorbidities with the potential to adversely affect TB treatment outcomes and quality of life. Dietary advice and nutritional management are components of comprehensive care for the above conditions as well as TB and should be included in planning of patient-centred services.